2022
DOI: 10.1097/mnh.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Ageing, cellular senescence and chronic kidney disease: experimental evidence

Abstract: Purpose of reviewChronic kidney disease (CKD) is often viewed as an accelerated and premature ageing of the kidney, as they share common pathological features characterized by cellular senescence. In this review, we summarize the experimental evidence linking cellular senescence to the pathobiology of kidney ageing and CKD, and discuss the strategies for targeting senescent cells in developing therapeutics for ageing-related kidney disorders. Recent findingsKidney ageing and CKD are featured with increased cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 94 publications
1
11
0
Order By: Relevance
“…The proinflammatory and profibrotic features of failed-repair PTCs are in good agreement with the senescence- associated secretory phenotype (SASP) reported in aged and injured nonkidney tissues [38]. Cellular senescence is involved in the pathogenesis of chronic kidney disease and senescence-targeting interventions displayed beneficial role in animal models of kidney ageing and disease [60,61 ▪ ,62,63]. However, the role of some features of cellular senescence in other systems has been controversial in the biology of failed-repair, in particular the role of cell cycle arrest.…”
Section: Altered Proximal Tubule Cells In Failed Tubule Repairsupporting
confidence: 71%
“…The proinflammatory and profibrotic features of failed-repair PTCs are in good agreement with the senescence- associated secretory phenotype (SASP) reported in aged and injured nonkidney tissues [38]. Cellular senescence is involved in the pathogenesis of chronic kidney disease and senescence-targeting interventions displayed beneficial role in animal models of kidney ageing and disease [60,61 ▪ ,62,63]. However, the role of some features of cellular senescence in other systems has been controversial in the biology of failed-repair, in particular the role of cell cycle arrest.…”
Section: Altered Proximal Tubule Cells In Failed Tubule Repairsupporting
confidence: 71%
“…However, the mortality of CKD patients is still high, and their life quality is low. Since senescence plays an important role in CKD, it could be Frontiers in Pharmacology frontiersin.org assumed as a new target for CKD treatment (Tan et al, 2022). The approach of targeting senescence is known as senotherapy, which mainly includes senolytics, senomorphics, and rejuvenating agents (Goligorsky, 2020).…”
Section: Targeting Renal Senescence In Therapy Of Ckdmentioning
confidence: 99%
“…Renal senescence and CKD share common characteristics and mechanisms, and there is a complex interactive relationship between them (Figure 4). Renal senescence is a promising target for therapeutic intervention of CKD, as preclinical data have shown the efficacy of senotherapies (Tan et al, 2022). In the future, more effective senotherapies and their judicious implementation are expected to fight against the progression of CKD or even reverse CKD, however, several challenges remained.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Moreover, other researchers confirmed that inhibition of tubular DNA damage and senescence could attenuate renal interstitial fibrosis after AKI, which was the key point of AKI progression to chronic kidney disease (CKD) [ 21 ]. In addition, senescent cells produce a complex secretome, known as the senescence-associated secretory phenotype (SASP), which promotes inflammation and the development of CKD [ 22 ]. Therefore, the removal of senescent cells by activating apoptosis appears to be a key mechanism for treating AKI and preventing the progression of CKD.…”
Section: Introductionmentioning
confidence: 99%